(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Electric vehicles (EVs) have gained significant attention as a promising solution to mitigate greenhouse gas emissions and reduce dependence on fossil fuels. The success of EV adoption is closely tied to the availability and efficiency of charging infrastructure. Quick charging technologies have emerged as a critical component in enhancing the practicality and convenience of EVs, enabling shorter charging times and longer driving ranges. This paper presents a comprehensive review of quick charging technologies for electric vehicles, focusing on the advancements, challenges, and future prospects in this rapidly evolving field